Waqf as an Instrument of Social Ethics: A Study of Islamic Legal Philosophy on Altruism and Ownership - Syifauddin, Moh. Nazih; Arifin, Bustanul; Piryanti, Meri (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background: In the tradition of Islamic law, waqf functions not only as an economic or social worship instrument but also as an embodiment of transcendent ethical values, emphasizing ownership as a trust and altruism as a social principle. However, the development of waqf studies in Indonesia remains largely dominated by technical, administrative, and productive-economic approaches, with limited attention to the underlying value structures and moral logic. Aim: This study aims to examine waqf as an instrument of social ethics within the framework of Islamic legal philosophy, focusing on three core concepts: ownership, altruism (īthār), and maqāṣid al-sharīʿah. Methods: This research employs a qualitative normative-philosophical approach using hermeneutics and textual analysis. Primary data are drawn from classical works such as those of al-Shāfiʿī, al-Ghazālī, Ibn ʿĀshūr, and Mutahhari, while secondary data are obtained from academic journals indexed in Scopus and SINTA. The analysis applies ontological, axiological, and epistemological readings of ownership concepts and waqf practices. Results: The findings reveal that waqf, in its philosophical sense, represents the relinquishment of private ownership as an act of spiritual devotion that bridges faith and social responsibility. Altruism in Islam is not merely a moral behavior but a structured ethic integrated within the Islamic legal system. Therefore, the understanding of waqf should be constructed not only through formal legal aspects but also as a reflection of the ethical logic of Islamic law, oriented toward public welfare and social justice.